2009
DOI: 10.1016/j.neuroscience.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The encoding of cocaine vs. natural rewards in the striatum of nonhuman primates: categories with different activations

Abstract: The behavioral and motivational changes that result from use of abused substances depend upon activation of neuronal populations in the reward centers of the brain, located primarily in the corpus striatum in primates. To gain insight into the cellular mechanisms through which abused drugs reinforce behavior in the primate brain, changes in firing of neurons in the ventral (VStr, nucleus accumbens) and dorsal (DStr, caudate-putamen) striatum to "natural" (juice) vs. drug (intravenous (IV) cocaine) rewards were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 65 publications
3
46
0
Order By: Relevance
“…encoding of stimulus-reward associations (18,19) and cue-induced reward expectation (20,21). Human functional neuroimaging data also demonstrate ventral striatal activity to cue presentation following appetitive and aversive Pavlovian conditioning (22).…”
Section: Discussionmentioning
confidence: 94%
“…encoding of stimulus-reward associations (18,19) and cue-induced reward expectation (20,21). Human functional neuroimaging data also demonstrate ventral striatal activity to cue presentation following appetitive and aversive Pavlovian conditioning (22).…”
Section: Discussionmentioning
confidence: 94%
“…This drug-induced effect of intravenous cocaine is in accord with the involvement of the dorsal striatum in reward and addiction 57 . Importantly, striatal DA release has been shown to differentially activate subpopulations of striatal neurons 50, 58 , and cocaine is well known to elicit neural activity in the region 59, 60 . Overall, the data demonstrate that glucose influx follows electrically stimulated and pharmacologically evoked DA release, likely in response to metabolic demand within the dorsal striatum.…”
Section: Resultsmentioning
confidence: 99%
“…Separate investigations conducted in rats have shown that cocaine administration consistently increases CBF 6466 and tissue oxygenation 66 in many brain regions, including the striatum. Furthermore, cocaine reward has been shown to increase cell firing in both the dorsal and ventral striatum of non-human primates 60 . The simultaneous measurements of glucose and DA at a single recording site reported herein are the first of their kind.…”
Section: Resultsmentioning
confidence: 99%
“…This finding, and our subsequent Daun02 inactivation results, support the hypothesis that during drug self-administration training, specific patterns of sparsely distributed neurons are selected by drug-associated contexts to form neuronal ensembles that encode learned associations between the contexts and drug effects (Cruz et al, 2013). In vivo electrophysiological recordings of single neurons during self-administration also suggest that different accumbens neurons are selectively activated by specific drug-associated contexts (and discrete cues) (Carelli et al, 1993;Peoples and West, 1996;Deadwyler et al, 2004;Opris et al, 2009;Guillem et al, 2013).…”
Section: Role Of Accumbens Shell Neuronal Ensembles In Contextinducedmentioning
confidence: 99%